PENGARUH PERILAKU BULLYING TERHADAP PERKEMBANGAN KEMAMPUAN SOSIAL PESERTA DIDIK DI SMK NEGERI 11 KABUPATEN TANGERANG - Aisyah, Nur; Rochani; Lenny Wahyuningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe bullying behavior, describe social skills, and examine the influence of bullying behavior on the social skills of tenth-grade students at SMK Negeri 11 Tangerang Regency. This study used a quantitative approach with a correlational research design. The population consisted of 216 tenth-grade students, and a sample of 120 students was selected using a random sampling technique. Data were collected through a Likert-scale questionnaire consisting of 48 statements and were analyzed using Pearson Product Moment correlation and simple linear regression with the assistance of SPSS software. The results showed that students' bullying behavior was generally in the moderate category (70.0%, or 84 students), and likewise, students' social skills were also in the moderate category (70.0%, or 84 students). The hypothesis test results showed a significance value of 0.001 (< 0.05) with a correlation coefficient of -0.393, indicating a significant negative relationship between bullying behavior and students' social skills. The simple linear regression results reinforced this finding with a regression coefficient (b) of -0.364, while the coefficient of determination (R Square) of 0.154 indicates that bullying behavior contributes 15.4% to students' social skills, with the remaining 84.6% influenced by other factors outside this study. Thus, it can be concluded that the higher the bullying behavior experienced or committed by students, the lower their social skills tend to be. The findings of this study are expected to serve as input for guidance and counseling teachers in designing programs to prevent bullying behavior and improve students' social skills.